Jorge Barradas e seus caprichos : conservação e restauro de um painel - Oliveira, Adriana Anselmo de, 1976- (2017)
Jorge Barradas (1894-1971) was an artist and ceramist, from the first generation of Por-tuguese modernists, well known from 1940 to 1970 for his innovations in modern wall glazed tiles. The present report aims at registering the interventions of conservation and restoration on a tile panel by this ceramist. The panel, which belongs to the collection of the Na-tional Tile Museum in Lisbon, is dated from 1963 and consists of a wall panel of glazed tiles with a decorative floral composition, one of a number of works referred to as Ca-prichos by the artist. The tiles, very fragmented, were subjected to analysis using energy dispersive X ray fluorescence spectroscopy (EDXRF), scanning electron microscopy with energy disper-sive spectroscopy (SEM-EDS) and Raman spectroscopy for material identification of the polychrome tile pieces. In this project, the historical research on the artist's work, the practice of intervention and the technical research were carried out simultaneously. The objectives were to un-derstand the panel's origin and its integration throughout the artist's whole work, the main characteristics of the materials used in the tiles, and, at the same time, preparing a diagnosis leading to the intervention and permitting future exhibition